Metagenome-assembled genomes from mineral tundra soils in Rásttigáisá, northern Norway - Pessi, Igor S.; Rutanen, Aino; Hultman, Jenni (Microbiology Society, 2025)
Microbial communities in tundra soils remain largely unknown despite their important roles in the cycling of greenhouse gases. Here, we report 59 non-redundant metagenome-assembled genomes (MAGs) recovered from mineral tundra soils in Rásttigáisá, northern Norway. The MAGs were obtained by clustering contigs according to tetranucleotide frequency and dif-ferential coverage and were manually curated to remove contigs with outlying GC content and/or mean coverage. Most MAGs were assigned to the bacterial phyla Candidatus Dormibacterota (n=12), Verrucomicrobiota (n=10), and Acidobacteriota (n=9). All archaeal MAGs (n=4) belong to the genus Candidatus Nitrosopolaris (phylum Thermoproteota). The 59 Rásttigáisá MAGs expand our knowledge of the diversity and ecological roles of tundra microbiomes. Peer reviewed